RESTORATIVE JUSTICE DALAM PERADAPAN HUKUM MODERN (Refleksi Nilai-nilai Agama Hindu) - Hartanto, Hartanto (Belom Bahadat, 2023)
Indonesia is a country of law that recognizes the existence of customary and religious law as a source of law. The daily practice of menusia is to communicate (naturally) but in this opinion and / communication often occurs speech that violates the rights of others or hurts other parties, then the potential for this conflict penetrates using spoken language on social media (internet). The regulation that regulates criminal acts related to defamation is Law No. 19 of 2016 concerning Electronic Information and Transactions, while the more general nature is the criminal code, which has "bridged" customary and religious law as living law into the criminal justice system as positive law. Currently, all law enforcement institutions have accommodated modern law by issuing rules on the use of restorative justice, in line with the nature of criminal law which is ultimum remedium. On the one hand, the old pradigma considered that legal certainty must be criminal proceedings and lead to imprisonment, but modern society with the aim of law yearns for peace and social harmony, which is also contained in Pancasila. The research cites several opinions of international and local figures; The results of this study show that the application of restorative justice is full of values and philosophical, so it is necessary to educate and legal awareness to solve this problem by involving the community, victims and perpetrators of crimes with the aim of achieving justice for all parties, because the essence of the law is the "property" of society.